2010
DOI: 10.3109/00016481003753448
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of gastric pepsinogen in middle ear fluid of children with glue ear

Abstract: Measurable pepsinogen was present in all MEEs from patients, with levels higher than the serum values. The difference between the levels of pepsinogen measured in MEE and serum was statistically significant (p < 0.01), but albumin levels were higher in serum than in MEE and the difference was statistically significant (p < 0.01).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 15 publications
1
27
0
Order By: Relevance
“…As an outcome of the study, they thought that pepsin may enter into middle ear through eustachian tube, and concluded that analysis of pepsin from middle ear effusion fluid samples may be a reliable diagnostic marker of LFR. [7] Toros et al analyzed human-specific pepsinogen 1 antibodies in the middle ear effusion fluid samples, and published results similar to those of Abdel-aziz et al [10] In a similar study Tasker et al reported that pepsin/pepsinogen levels measured in the middle ear effusion fluid might increase up to 1000 times when compared with their serum levels. [11] Hellgren et al evaluated risk factors (i.e.…”
Section: Discussionsupporting
confidence: 58%
“…As an outcome of the study, they thought that pepsin may enter into middle ear through eustachian tube, and concluded that analysis of pepsin from middle ear effusion fluid samples may be a reliable diagnostic marker of LFR. [7] Toros et al analyzed human-specific pepsinogen 1 antibodies in the middle ear effusion fluid samples, and published results similar to those of Abdel-aziz et al [10] In a similar study Tasker et al reported that pepsin/pepsinogen levels measured in the middle ear effusion fluid might increase up to 1000 times when compared with their serum levels. [11] Hellgren et al evaluated risk factors (i.e.…”
Section: Discussionsupporting
confidence: 58%
“…[12] Several researchers have shown that a significant number of children with OME had concurrent GER disease and some others demonstrated that children with GER disease displayed a high prevalence for OEM. Toros et al [13] demonstrated that pepsinogen levels in patients with chronic serous otitis media with GER symptoms were higher than in those without GER symptoms. Rozmanic et al [14] found that 55.6% of children with OME had concurrent GER disease.…”
Section: Discussionmentioning
confidence: 99%
“…[11] Laryngopharyngeal reflux can lead to chronic otitis media with effusion (OME), which is characterized by the presence of a middle ear effusion in the middle ear space for 3 months or longer. [12] Acid reflux is thought to cause inflammation of the nasopharynx, dysfunction of the Eustachian tube, and impairment of the mucociliary clearance, thus leading to increase in the incidence of OME. [13]…”
Section: Signs and Symptomsmentioning
confidence: 99%